Strategi Marketing Public Relations Senayan Golf Club Dalam Membangun Brand Awareness - Adhara Putri Prasanty; Lilik Sumarni (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Senayan Golf Club is a commercial business that is now growing as many people are aware of the importance of maintaining health by exercising. Even Golf has now become a lifestyle by various groups, especially millennials. More and more golf courses are spread in various regions in Indonesia due to the increasing number of golf enthusiasts. Although Senayan Golf Club is one of the 7 best golf courses in Jabodetabek, Senayan Golf Club must be ready to compete with other competitors. Therefore, it requires the role of Marketing Public Relations in building Brand Awareness of Senayan Golf Club based on the Three Ways Strategy namely Push, Pull, Pass Strategy (Ruslan, 2016). In an effort to carry out the functions and roles of Marketing Public Relations, the right strategy is needed. This research uses a descriptive qualitative approach and in-depth interview methods and documentation. Informants in this study are Head of Marketing communication and Social Media Specialist. The results of the research strategies used by Marketing Public Relations in building Brand Awareness Senayan Golf Club are push through publications and promotions through social media, the second strategy is pull by creating educational content and tutorial videos that are interesting and relate to Golf lovers. The third strategy is pass (influence) by building a good image, creating events and tournaments, and working with third parties and sponsorships.